PENERAPAN ALGORITMA SEQUENTIAL SEARCH PADA CHATBOT WHATSAPP UNTUK LAYANAN PENGADUAN APLIKASI SMEP - Rahmawati, Dwi; Setyawan, Mohammad Bhanu; Prasetyo, Angga (Jurnal Media Elektro, 2024)
SMEP, or Reporting Evaluation Monitoring System is a web-based application designed to provide information on the progress of goods and services procurement within the Ponorogo Regional Government. Currently, consultations related SMEP are conducted manually through the WhatsApp platform, but there is no mechanism to process information from the submitted reports. The Development Administration Divisioon identified the need to develop a chatbot whatsapp complaint service application, to strengthen interactive relationship with users. This application implements the Sequential Search algorithm to accelerate the database search process, aiming to significantly improve the quality of SMEP services. The development method used is Research and Development (R&D) with waterfall model development procedures. The Application was tested for functional suitability using media validity test sheets and obtaining a 100% validity percentage. Usability testing, using a questionnaire with 50 SMEP application users, resulted in an 89.67% validity persentage, thus qualifying as “Very Worthy” on the Likert scale. Based on testing results, it can be concluded that the Whatsapp chatbot for SMEP complaint services, which implements the sequential search algorithm, is highly effective and make positive contribution to improving the efficiency and effectiveness of SMEP services.